Electric field modulation of light energy transmission along intermediate filaments isolated from porcine retina - Khmelinskii, Igor (2021)
Presently we report new experimental method for simultaneous measurements of electrical and optical properties in vitro for the intermediate filaments (IFs) in the axial direction, complemented by the method to measure light intensity absorbed by IFs aligned within the capillary matrix. These methods were used to simultaneously measure spectroscopic and electric properties of Müller cell (MC) IFs extracted from porcine retina. Using light at 546 nm, we found that these IFs are excellent conductors of light energy, with the efficiency of ca. 0.5 without external voltage field and 0.7 in presence of an external voltage of 0.1 V, and good conductors of electric current, with the conductivity value close to that of typical metals. We also found that the efficiency of light energy transmission along IFs depends on the external applied voltage. The presently reported optical and electrical properties of MC IFs may endow vertebrate eyes with high-contrast vision, providing evidence in favor of a mechanism regulating the amount of light energy transmitted via MC IFs between inner and outer limiting membrane levels in vertebrate retina.